Long-chain SFA at the sn-1, 3 positions of TAG reduce body fat deposition in C57BL/6 mice - Chuah, Cheng Hock; Gouk, S.W.; Cheng, S.F.; Mok, J.S.L.; Ong, A.S.H. (Cambridge University Press, 2013)
The present study aimed to determine the effect of positional distribution of long-chain SFA in TAG,especially at the sn-1, 3 positions, on fat deposition using the C57BL/6 mouse model. Throughout the 15 weeks of the study, mice were fed with diets fortified with palm olein (POo), chemically interesterified POo (IPOo) and soyabean oil (SOY). Mice receiving the SOY-enriched diet gained significantly higher amounts of subcutaneous fat (P═0·011) and total fat (P═0·013) compared with the POo group,despite similar body mass gain being recorded. During normalisation with food consumption to obtain the fat:feed ratio, mice fed with the POo-enriched diet exhibited significantly lower visceral (P=0·044), subcutaneous (P=0·006) and total (P=0·003) fat:feed than those fed with the SOY-enriched diet. It is noteworthy that mice fed with the IPOo-enriched diet gained 14·3% more fat per food consumed when compared with the POo group (P=0·013), despite their identical total fatty acid compositions. This was mainly attributed to the higher content of longchain SFA at the sn-1, 3 positions of TAG in POo, which results in delayed absorption after deacylation as evidenced by the higher amounts of long-chain SFA excreted in the faeces of mice fed with the POo-enriched diet. Negative correlations were found between the subcutaneous, visceral as well as total fat accretion per food consumption and the total SFA content at the sn-1, 3 positions, while no relationships were found for MUFA and PUFA. The present results show that the positional distribution of long-chain SFA exerts a more profound effect on body fat accretion than the total SFA content.